Directors' dilemmas tales from the frontline - Dunne, Patrick; Gale Group (London Kogan Page, 2005)
Offers expert advice to directors on the nature of dilemmas and principles for resolving them. Describes twenty real-life wrangles and clashes in detail, and offers solutions. The full range of companies is represented in these genuine dilemmas, from the fledgling start-up to the mature multi-national corporation.
Electronic reproduction.
Keywords: Directors of corporations; Industrial management; Decision making -- Case studies; Electronic books